2021
DOI: 10.3390/antiox10030468
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus delbrueckii Protected Intestinal Integrity, Alleviated Intestinal Oxidative Damage, and Activated Toll-Like Receptor–Bruton’s Tyrosine Kinase–Nuclear Factor Erythroid 2-Related Factor 2 Pathway in Weaned Piglets Challenged with Lipopolysaccharide

Abstract: Oxidative stress is increasingly being recognized as a player in the pathogenesis of intestinal pathologies, and probiotics are becoming an attractive means of addressing it. The present study investigated the effects of dietary supplementation with Lactobacillus delbrueckii (LAB) on intestinal integrity and oxidative damage in lipopolysaccharide (LPS)-challenged piglets. A total of 36 crossbred weaned piglets (Duroc × Landrace × Large Yorkshire) were randomly divided into three groups: (1) non-challenged cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Our study showed KDP supplementation exhibited a potent antioxidant activity, as indicated by significant inhibitory activity in the range of 16.52-59.39% for DPPH, nitric oxide, maximum total antioxidant capacity, and maximum reducing power. This agrees with the results of several other studies showing that LAB plays a vital role in the ameliorative antioxidant capacity in different models [40][41][42][43]. In addition, several studies have shown that different strains of LAB activate the immune system and subsequently protect the body against bacterial and viral infection [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed KDP supplementation exhibited a potent antioxidant activity, as indicated by significant inhibitory activity in the range of 16.52-59.39% for DPPH, nitric oxide, maximum total antioxidant capacity, and maximum reducing power. This agrees with the results of several other studies showing that LAB plays a vital role in the ameliorative antioxidant capacity in different models [40][41][42][43]. In addition, several studies have shown that different strains of LAB activate the immune system and subsequently protect the body against bacterial and viral infection [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…At this regard, experimental studies showed that bovine epithelial cells treated with scalar doses of LPS showed a significant reduction of antioxidant enzymes activity, such as GPx3, SOD and catalase (29). Similarly, a study investigating intestinal oxidative stress in piglets challenged with LPS, showed a decrease of SOD, catalase and GPx activity, which was blunted by probiotic supplementation (30). Furthermore, considering that an agingrelated decline in the activity of GPx enzymes has been previously reported (31,32), it is also conceivable that the oxidative damage related to LPS may be even more evident in elderly patients with a high atherothrombotic burden (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this index is often used in clinical and actual production to reflect the anoxia of intestinal body, intestinal mucosal damage, and intestinal mechanical barrier [ 40 ]. Once the intestinal barrier is disrupted, the intestinal epithelium releases DAO and D-LA into the bloodstream, and these are employed as indicators for intestinal integrity [ 41 , 42 ]. Our results showed that the levels of both DAO and D-LA were elevated in the A. adenophora -treated groups as compared to the control group, and this indicated that A. adenophora could cause destruction of intestinal integrity and epithelial function.…”
Section: Discussionmentioning
confidence: 99%